Applications of the H-reflex in kinesiology: a systematic review - Gajos Agnieszka; Kujawski Sławomir; Gajos Małgorzata; Chatys Żaneta; Bogacki Piotr (Sciendo, 2014)
Study aim: discussion of applications of H-reflex in kinesiology.